Judicial ombudsman for subordinate judiciary in India - Nath, Kamleshwar (2011)
Administration of justice is under sharp and critical gaze of people today because of ever -incresing number of court cases and the inordinate delays in their resolution. A perfect picture of people's disillusionment and unrest with the system emerges when corruption also comes into play with the delays. Brunt of the heaviest burden of dispensation is borne by subordinate courts. A careful balance between judiciary's accountability towards people and its independence needs to be ensured. It can be provided by appointment of judicial ombudsman for various levels.The very existence of the ombudsman's office can instill a sense of caution among the subordinate judiciary and promote better performance both on the judicial and administrative side. - Reproduced.
Keywords: Judiciary - India; Ombudsmen - India; Corruption - India; Corruption